Reimagining social relations through care and collective joy: The formation of collectivity among volunteers along the lines of in/formality - Brunßen, M.; Jay, S.; Oliveira, J. M. de. (Journal of Community and Applied Social Psychology, 2026)
The neoliberal model of social organisation frames individualism as the dominant perspective to perceive the world and competition as its core practice. Interdependencies become marginalised, and ideas of social welfare and community are pushed aside. Mutual aid efforts not only aim to provide relief for resulting social inequalities but further seek to build new social relations. Adopting a feminist institutionalist approach, this paper aims to contribute to a move away from neoliberal structuring of social relations by analysing how collectivity among volunteers is formed. Based upon ethnographic fieldwork and eight interviews with volunteers in the context of Lesvos, Greece, this paper contextualises the role of collectivity among volunteers working in mutual aid organisations along the lines of in/formalities. It provides a deeper understanding of the role of affect by exploring practical tools through which affective collectivity is formed: care and collective joy. The paper argues that in/formalities are not distinct spheres but, much like the private-public domains, constantly flow into and influence each other. While extending previous psychological research, the present paper shows that practices of care and collective joy, intertangled with in/formalities, offer possibilities to form affective mutual relationships between volunteers and are an integral part of collectivity formation.